Modelo de Simulación Dinámica para el Diagnóstico de la PYME - Méndez Giraldo, Germán Andrés; Álvarez Pomar, Lindsay; Kalenatic, Dusko (Ingeniería, 2004)
This paper shows the results of the first phase of research «Structure of Integral Diagnostic System to Small and Medium Enterprise Focused by Dynamics Systems». In this phase has been designed, developed and systematized model to Pymes diagnostic, which combines different kind of continuously simulation models in each of seven functional areas to divide a productive organization such as: Quality, Financial, Environment, Marketing, Production, Human Resources and Technology. These models can understand separated de good or bad management in these functional areas. We built and integral diagnostic model to Pyme in an simulation environment, which it linking Industrial Dynamic concepts and system focused in order to support financial decisions to minimized risk of Pyme's loans and as a tool of diagnosis and business improvement. In addition, was possible to get a cumulus of characteristic, relations and rules to build knowledge base, in order to develop an Expert Diagnostic System in a future.